Pengolahan Minuman Serbuk Instan Buah Naga Merah Hylocereus Polyrhizus Dengan Metode Ko-Kristalisasi - Anugrah, Salsabila Permata; Laga, Suriana; Abriana, Andi (Fakultas Pertanian Universitas Bosowa, 2025)
Red dragon fruit has bioactive substances such as antioxidants (ascorbic acid, beta-carotene and anticyanin) and pectin which has dietary fiber which is good for the body. Processing instant products using the co-crystallization method can be done by adding sucrose and fillers such as maltodextrin and vegetable creamer. Maltodextrin aims to coat the flavor components and organoleptic properties of instant powder products. Vegetable creamer is used as a flavoring for food and drinks. The aim of the research is to determine the effect of adding vegetable creamer on water content, sugar content, and organoleptic tests which include color, aroma, and taste. The research treatments carried out in this study were the addition of 0%, 12%, 17%, and 22% vegetable creamer. The research parameters are, water content, sugar content, organoleptic tests including color, aroma, and taste. The design used was a Completely Randomized Design (CRD), with three replications. The further test used is the Least Significant Difference Test (LSD). The best treatment was the addition of 22% vegetable creamer in terms of taste, namely 3,33 (rather like it). The water content in instant red dragon fruit powder drinks ranges from 3.44%-3.75%, not yet meeting the requirements according to SNI 01-4320-2004 for powdered drinks of 3%; meanwhile, the sugar content meets the requirements. Buah naga merah mempunyai zat bioaktif seperti antioksidan (asam askorbat, betakaroten, dan antisianin) serta pektin dimana memiliki serat pangan yang baik bagi tubuh. Pengolahan produk instan dengan metode ko-kristalisasi dapat dilakukan dengan adanya penambahan sukrosa dan bahan pengisi seperti maltodekstrin dan krimer nabati. Maltodekstrin bertujuan untuk melapisi komponen flavor dan sifat organoleptik produk instan serbuk. Krimer nabati dipergunakan sebagai padanan rasa untuk makanan dan minuman. Tujuan penelitian yaitu untuk mengetahui pengaruh penambahan krimer nabati terhadap kadar air, kadar gula, dan uji organoleptik yang meliputi warna, aroma, dan citarasa. Perlakuan penelitian yaitu penambahan krimer nabati 0%, 12%, 17%, dan 22%. Parameter penelitian yaitu kadar air, kadar gula, dan uji organoleptik meliputi warna, aroma, dan citarasa. Rancangan yang digunakan yaitu Rancangan Acak Lengkap (RAL), dengan tiga kali ulangan. Uji lanjutan yang digunakan ialah Uji Beda Nyata Terkecil (BNT). Perlakuan terbaik yaitu penambahan krimer nabati 22% ditinjau dari cita rasa yaitu 3,33 (agak suka). Kadar air pada minuman serbuk instan buah naga merah yaitu berkisar antara 3,44%-3,75% belum memenuhi SNI 01-4320-2004 minuman serbuk sebesar 3%; sedangkan kadar gula telah memenuhi.